Pengaruh Service Marketing, Relationship Marketing, Communication Marketing terhadap Customer Satisfaction - Chandra Kartika; Devita Anggraeni (Program Studi Manajemen Dakwah Fakultas Dakwah dan Komunikasi UIN Sunan Ampel Surabaya, UIN Sunan Ampel Surabaya, 2022)
This study aims to determine: Is there any influence of Service Marketing, Relation Marketing and Communication Marketing simultaneously affect the Customer Satisfaction of Motorcycle users at Surya Gemilang Motor Surabaya Barat, Is there any influence of Service Marketing partially affect the Customer Satisfaction of Motorcycle users at Surya Gemilang Motor Surabaya West, Is there any influence of Relationship Marketing which partially affects Customer Satisfaction of Motorcycle users at Surya Gemilang Motor , W est Surabaya, Is there any influence of Communication Marketing that partially affects Customer Satisfaction of Motorcycle users at Surya Gemilang Motor, West Surabaya. The population in this study are customers who use Honda motorcycles. The sampling technique used was accidental sampling. The data collection technique used a questionnaire that had been tested for validity and reliability. The data analysis technique used is multiple regression. The results of this study indicate that Service Marketing, Relation Marketing and Communication Marketing variables simultaneously have a Positive and Significant effect on Customer Satisfaction of Motorcycle users at Surya Gemilang Motor, West Surabaya. Relationship Marketing partially has no effect on Customer Satisfaction of Motorcycle users at Surya Gemilang Motor, West Surabaya. Keywords: Service marketing, relationship marketing, marketing communication, customer satisfaction